Sanguinarine Induces Apoptosis Pathway in Multiple Myeloma Cell Lines via Inhibition of the JaK2/STAT3 Signaling - Akhtar, Sabah; Achkar, Iman W.; Siveen, Kodappully S.; Kuttikrishnan, Shilpa; Prabhu, Kirti S.; Khan, Abdul Q.; Ahmed, Eiman I.; Sahir, Fairooz; Jerobin, Jayakumar; Raza, Afsheen; Merhi, Maysaloun; Elsabah, Hesham M.; et al. (Frontiers in Oncology, 2019)
Sanguinarine (SNG), a benzophenanthridine alkaloid, has displayed various anticancer abilities in several vivo and in vitro studies. However, SNG anticancer potential has yet to be established in multiple myeloma (MM), a largely incurable malignancy of plasma cells. In this study, we aimed to investigate the potential anti-proliferative and pro-apoptotic activities of SNG in a panel of MM cell lines (U266, IM9, MM1S, and RPMI-8226). SNG treatment of MM cells resulted in a dose-dependent decrease in cell viability via inducing the intrinsic apoptotic pathway through mitochondrial membrane potential loss and activation and cleavage of caspase 3, 9 and PARP. Pre-treatment of MM cells with a universal caspase inhibitor, Z-VAD-FMK, prevented SNG mediated cell viability, apoptosis, and caspase activation, confirming that SNG-mediated apoptosis is caspase-dependent. The SNG-mediated apoptotic effects appear to result from suppression of the constitutively active STAT3 with a concomitant increase in expression of protein tyrosine phosphatase (SHP-1). SNG treatment of MM cells leads to down-regulation of the anti-apoptotic cyclin D, Bcl-2, BclxL, and XIAP. Moreover, it upregulates Bax the pro-apoptotic protein. SNG mediated MM cellular DNA damage in MM cell lines by induction of oxidative stress through generation of reactive oxygen species and depletion of glutathione in these cells. Finally, the subtoxic concentration of SNG enhanced the cytotoxic effects of anticancer drugs Bortezomib (BTZ) by suppressing the viability of MM cells via induction of caspase-mediated apoptosis. Altogether our findings demonstrate that SNG induces mitochondrial and caspase-dependent apoptosis, generates oxidative stress, and promotes cell damage and suppresses MM cell lines proliferation. In addition, co-treatment of MM cell lines with sub-toxic doses of SNG and BTZ potentiated the cytotoxic activity. These results wiuld suggest that SNG could potentially use as a therapeutic compound against MM either alone or in combination with other anticancer drugs in MM.